2010
DOI: 10.5114/aoms.2010.13506
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plantar pressure and balance in patients with diabet

Abstract: IntroductionPatients with diabetes for more than 10 years may have an increase in peak plantar pressure, considerable postural oscillation, balance deficit, alterations in gait pattern and an increased risk of falls. The aim of the present study was to assess the correlation between plantar pressure distribution and balance in patients with diabetes using a pressure platform (Footwork).Material and methodsThe study was carried out at the Human Movement Clinic of the Centro Universitário de Belo Horizonte (Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Changes in foot pressures can be determined by assessing peak plantar pressures or pressure-time integral [5]. Although Anjos et al reported that patients living with diabetes for more than 10 years may have increased peak plantar pressure [9], which is also supported by Tuna et al [10], there is a clear paucity of information regarding this matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in foot pressures can be determined by assessing peak plantar pressures or pressure-time integral [5]. Although Anjos et al reported that patients living with diabetes for more than 10 years may have increased peak plantar pressure [9], which is also supported by Tuna et al [10], there is a clear paucity of information regarding this matter.…”
Section: Introductionmentioning
confidence: 99%
“…Limited joint mobility [4,5], structural foot deformities [6], intrinsic muscle weakness [7], and muscle atrophy [8] occur in both type 1 and type 2 diabetes. These complications may occur as a result of hyperglycemia and play a significant role in increasing plantar pressures [9].…”
Section: Introductionmentioning
confidence: 99%
“…The participants performed the test barefoot, with eyes open. Each data collection time was 30 seconds (19). The COP parameters assessed in this study were COP velocity (cm/ sec) and COP length (cm).…”
Section: Balance Evaluationmentioning
confidence: 99%
“…Therefore, this study used the Shoe Type Stabilometer that can measure CoP and plantar pressure in the natural standing position [6,9]. …”
Section: Discussionmentioning
confidence: 99%
“…One reason for this lack of findings may be that subjects in these studies were restricted to patients with disease or several young participants able to use large equipment (e.g. force plate, threedimensional (3D) motion analyzer) [5,6].…”
Section: Introductionmentioning
confidence: 99%